Bimetallic Metal-Organic Framework Derived Metal-Carbon Hybrid for Efficient Reversible Oxygen Electrocatalysis - Zhou, Yu; Zhang, Yan; Xu, Xianzhen; Zhao, Shenlong; Guo, Ziyi; Wu, Kuang-Hsu; Tan, Chunhui; Wang, Zonghua (Frontiers in Chemistry, 2019)
Development of cost-effective electrocatalysts for oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) is key to enabling advanced electrochemical energy conversion technologies. Here, a novel nitrogen-doped metal-carbon hybrid (NiCo/CN) with a unique 3D hierarchical structure, consisting of uniformly distributed bimetallic nanoparticles encapsulated by partially graphitized N-doped carbon shells, is fabricated by a one-step pyrolysis of a nanoscale metal-organic framework as precursor, which exhibits excellent activity for both ORR and OER. The surface chemical changes on the carbon hybrid probed by X-ray photoelectron spectroscopy (XPS) reveal the presence of favorable electronic interaction at the metal-nitrogen-carbon interface. Remarkably, the NiCo/CN catalyst prepared at high temperature (800°C) manifests a comparable performance to a commercial Pt/C catalyst for the ORR, but also superior stability, path selectivity and methanol tolerance. On the other hand, the Eonset (1.48 V vs. reversible hydrogen electrode) and Ej=10mA/cm2 of NiCo/CN-800 for OER is very close to the state-of-the-art noble catalyst RuO2 (Eonset = 1.46 and Ej=10mA/cm2) along with superior stability over 20 h of operation. The excellent catalytic property is attributable to the unique nanostructure, high porosity and the constructive synergistic effects of the elements M, N, and C.